Study of Behavioural Activity and Cognitive Impairment in Rats in the Simulation of Pneumococcal Meningitis - Alina A. Agarkova; Mikhail V. Pokrovsky; Pavel D. Kolesnichenko (Кубанский научный медицинский вестник)
Aim. To study neurological disorders in rats when modeling purulent bacterial meningitis (PBM) on the example of pneumococcal meningitis under experimental conditions.Materials and methods. Pneumococcal meningitis was modeled by injecting a suspension containing Streptococcus pneumoniae at a concentration of 5×109 CFU/ml into the subarachnoid space. The degree of neurological disorders was determined by clinical assessment of rat health status, the degree of neurological defi cit, specifi c strength, “Infrared activity monitor”, “Object recognition task” tests.Results. When modeling pneumococcal meningitis in rats, the sum of points of clinical assessment of their health in the 1st day after modeling the pathology is 34.2 % less than the initial, on the 5th — less than 3.4 %, on the 8th day returns to the primary indicator, 5 points. The maximum degree of severity of neurological defi cit was observed in the fi rst four days after meningitis modeling; it was in the 1st day 34 % less than the same indicator in the group of intact animals, on the 2nd day 32.7 % less, on the 3rd day — 30.7 % and on the 4th day — 30.1 %. In the meningitis group on day 10, the distribution of neurological defi cit by severity was as follows: mild — 32 %, medium — 20 %, severe — 16 %, without residual neurological defi cit — 32 %. The specifi c strength of rats in the group of meningitis on the 1st, 5th and 10th day after the development of the pathology was 48.7, 64, and 67.4 % of the baseline specifi c strength. In relation to intact animals, the index of recognition of short-term memory in rats of the meningitis group is 2.3 times greater, and the index of recognition of long-term memory is 1.7 times greater.Conclusion. The dynamics of neurological disorders in rats in the simulation of PBM can be determined using the methods of assessing behavioural and cognitive status. In rats, when modeling pneumococcal meningitis, neurological disorders are maximally expressed on the 1st day of the disease. Then there is a distinct positive dynamic up to 5 days of the disease. From 6 to 10 days positive dynamics is present, but insignifi cant.